Financial imbalances and household welfare: empirical evidence from the EU - Livio Stracca (European Central Bank (ECB), 2013)
This paper uses Eurobarometer survey data from 26 EU countries to evaluate whether the general public cares about financial stability and imbalances over and above their effects on key macroeconomic variables such as unemployment and inflation. I confirm previous results in the literature that life satisfaction - a widely used measure of household welfare - negatively depends on the unemployment rate. In addition to previous results in the literature, I establish a strong empirical link between life satisfaction and consumer confidence as measured by the European Commission consumer survey. The main result of the paper is that life satisfaction generally does not systematically depend on a number of measures of financial imbalance based on credit and asset prices once the other macroeconomic controls are included.
Keywords: E6; 330; Central Bank; Consumer Confidence; Eurobarometer; financial stability; life satisfaction